A Comparative Study of Two Endemic Isoëtes Species from South Italy. (14th November 2012) - Ernandes, Paola; Marchiori, Silvano
Abstract : Two Isoëtes taxa (Isoëtaceae, Pteridophyta) have recently been described in Puglia and Sicily (south Italy). Though morphologically similar (Ernandes, 2011), they differ in diagnostic characters and habitat preferences. In this paper, we highlight the differences and similarities between Isoëtes iapygia Ernandes, Beccarisi et Zuccarello (Ernandes et al., 2010) and Isoëtes todaroana Troia et Raimondo (Troia and Raimondo, 2009). Individuals are described in terms of selected diagnostic characters. Morphometric differences and other distinguishing characteristics suggest that I. iapygia and I. todaroana should be considered as separate species.